Loss of CMD2‐mediated resistance to cassava mosaic disease in plants regenerated through somatic embryogenesis. (5th April 2016) - Beyene, Getu; Chauhan, Raj Deepika; Wagaba, Henry; Moll, Theodore; Alicai, Titus; Miano, Douglas; Carrington, James C.; Taylor, Nigel J.
Summary: Cassava mosaic disease (CMD) and cassava brown streak disease (CBSD) are the two most important viral diseases affecting cassava production in Africa. Three sources of resistance are employed to combat CMD: polygenic recessive resistance, termed CMD1, the dominant monogenic type, named CMD2, and the recently characterized CMD3. The farmer‐preferred cultivar TME 204 carries inherent resistance to CMD mediated by CMD2, but is highly susceptible to CBSD. Selected plants of TME 204 produced for RNA interference (RNAi)‐mediated resistance to CBSD were regenerated via somatic embryogenesis and tested in confined field trials in East Africa. Although micropropagated, wild‐type TME 204 plants exhibited the expected levels of resistance, all plants regenerated via somatic embryogenesis were found to be highly susceptible to CMD. Glasshouse studies using infectious clones of East African cassava mosaic virus conclusively demonstrated that the process of somatic embryogenesis used to regenerate cassava caused the resulting plants to become susceptible to CMD. This phenomenon could be replicated in the two additional CMD2‐type varieties TME 3 and TME 7, but the CMD1‐type cultivar TMS 30572 and the CMD3‐type cultivar TMS 98/0505 maintained resistance to CMD after passage through somatic embryogenesis. Data are presented to define the specific tissue culture step at which the loss of CMD resistance occurs and to show that the loss of CMD2‐mediated resistance is maintained across vegetative generations. These findings reveal new aspects of the widely used technique of somatic embryogenesis, and the stability of field‐level resistance in CMD2‐type cultivars presently grown by farmers in East Africa, where CMD pressure is high.